An integrated approach for solving cell formation and intra-cell machine layout problem considering operation sequence and alternative process routing. (9th December 2020) - Raja, S.
Cellular manufacturing is a group technology approach wherein parts and machines are arranged in flow production. Most of the cell formation methods in the previous literature have addressed the zero-one matrix for solving cell formation problem with single process routing. Even though multiple routings are considered in some cases, machine layout is not considered which results in increased number of backward flow, voids and exceptional elements. In this research, we have proposed a new heuristic approach for solving cell formation problem based on new similarity coefficient method and identifying intra-cell machine layout based on flow matrix by considering operation sequence and alternative routings. In order to validate the efficiency of our proposed method, five well-known test problems from the literature are employed and the results are compared with the existing method the results clearly show that the proposed approach which that provides superior or equal solution than the existing method.